2018
DOI: 10.1507/endocrj.ej17-0401
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diverse complications and its association with karyotypes in Japanese adult women with Turner syndrome—a questionnaire survey by the Foundation for Growth Science—

Abstract: The reported prevalence of complications in Turner Syndrome (TS) was highly variable because of the rarity and the limited numbers analyzed. Again, possible presence of other complications that are not described as specific for TS, is also speculated. To resolve these issues, a questionnaire survey was conducted in hGH treated 492 patients with adult TS (17-42 years). The possible association with these complications and karyotypes were also analyzed. The complications and their prevalence were as follows: chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…Consistent with most (17,25,35,37), but not all previous studies (26,27,29,32,38), autoimmune thyroid disease was more frequently observed in 45,X/46,isoXq and 45,X patients. Our findings also provide the first precise information about the increase in celiac disease frequency with age in patients with 45,X/46,isoXq, 46,X,r(X)/46,XX and 45,X karyotypes.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Consistent with most (17,25,35,37), but not all previous studies (26,27,29,32,38), autoimmune thyroid disease was more frequently observed in 45,X/46,isoXq and 45,X patients. Our findings also provide the first precise information about the increase in celiac disease frequency with age in patients with 45,X/46,isoXq, 46,X,r(X)/46,XX and 45,X karyotypes.…”
Section: Discussionsupporting
confidence: 84%
“…The importance of X chromosome gene dosage as a risk factor for congenital and acquired comorbid conditions was not previously recognized in some studies, as the relatively small number of patients studied and differences in patient age made it difficult to describe the complete spectrum according to karyotype accurately (11,12,13,14,15,16,17,18,19,20,26,27). For acquired conditions, some studies focused on pediatric patients only (12,16,20), whereas others analyzed young or middle-aged women (14,28,29,30,31). Moreover, with few exceptions (26,27,32,33,34,35), most of these studies were transverse in nature, precluding the evaluation of age at onset for each comorbidity and the relationship to the different karyotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The X-chromosome contains several genes involved in neuronal morphogenesis, neuroanatomical abnormalities, and epilepsy [2]. However, epilepsy is unusual in TS, with a morbidity rate of approximately 2-3% [3,4]. TS with epilepsy is frequently associated with structural brain abnormalities and mosaicism karyotype [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Stoklasova et al analyzed the relation between karyotypes and autoimmune diseases in a cohort of 286 Czech TS females and found that isolated Xp deletion and triple X mosaicism are related to an increased risk of AITDs [33]. Nevertheless, other authors did not find any evidence of correlation between TS karyotypes and autoimmune diseases [37,39,[42][43][44][45]47,48,54,55,57,78,89] (Table 1).…”
Section: Turner Syndromementioning
confidence: 99%